2020
DOI: 10.4102/phcfm.v12i1.2474
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, healthcare costs and management of non-communicable diseases in people living with human immunodeficiency virus: A scoping review

Abstract: Background: Coexistence of human immunodeficiency virus (HIV) and non-communicable diseases (NCDs) is an important public health issue of increasing concern. However, the prevalence, healthcare costs and management protocols for NCDs in people living with HIV (PLHIV) remain unclear in most settings.Aim: To scope evidence on prevalence, healthcare costs and disease management protocols associated with NCDs in PLHIV from studies published before July 2019.Methods: Electronic databases were searched for published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
(45 reference statements)
1
6
0
Order By: Relevance
“…The main finding and key message of our study is the very high prevalence of HTN in PLWH despite their young age (almost 20%), of whom almost half are unaware of their condition. The prevalence of 17.5% in our population is comparable to those reported in Nigeria 29 , Zimbabwe 30 , South Africa 31 Zambia 32 and Tanzania 33 , but lower than those reported in Uganda 34 , Cameroon 35 , Brazil 36 , China 17 , 18 Ugandan rural study 37 and Argentina 38 . Similarly, our findings are higher than those reported in Ethiopia 16,39,40 and Kenya 41 .…”
Section: Discussionsupporting
confidence: 69%
“…The main finding and key message of our study is the very high prevalence of HTN in PLWH despite their young age (almost 20%), of whom almost half are unaware of their condition. The prevalence of 17.5% in our population is comparable to those reported in Nigeria 29 , Zimbabwe 30 , South Africa 31 Zambia 32 and Tanzania 33 , but lower than those reported in Uganda 34 , Cameroon 35 , Brazil 36 , China 17 , 18 Ugandan rural study 37 and Argentina 38 . Similarly, our findings are higher than those reported in Ethiopia 16,39,40 and Kenya 41 .…”
Section: Discussionsupporting
confidence: 69%
“…Twenty-eight articles in the review identified barriers to diagnosing NCDs (hypertension and diabetes). 14 , 15 , 20 , 35 61 The included studies reported barriers to and facilitators of diagnosing depression among PLWH. 42 , 50 , 62 73 Two studies reported both NCDs and depression.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Three studies from Zambia, Mozambique, and Zimbabwe reported the limited capacity of ART clinics and lack of health system readiness for NCD services. 36 , 56 , 58 …”
Section: Physical Opportunitymentioning
confidence: 99%
“…Research indicates that in older PLHIV, the burden of multimorbidity and polypharmacy is more linked to the duration of HIV infection than to advanced age itself. 8 The non-communicable comorbidities in older PLHIV include metabolic disordershypertension and hyperlipidemia, 9,10 cardiovascular diseases, 11,12 anemia, 10 kidney disease, 13 and age-related conditions, 14 such as cognitive impairment, [15][16][17][18] frailty, [18][19][20] bone disease, 21 multimorbidity 8,10,[22][23][24][25][26] and polypharmacy, 7,10,[26][27][28][29] but are not limited to those listed. Furthermore, studies have shown that in older patients, mental health issues often coexist with physical medical conditions.…”
Section: Introductionmentioning
confidence: 99%